Does repair of pronator quadratus muscle after volar plating change the functional outcome in patients with distal radius fracture? - Onta, Pratyenta Raj; Ranjeet, Niraj; Sapkota, Krishna; Wahegaonkar, K; Thapa, P; Thapa, UJ (Nepal Orthopaedic Association Journal, 2020)
INTRODUCTION: Fracture of distal radius is a common fracture and the treatment modality varies from conservative to operative technique. Volar plating is a common operative fixation for distal radius fracture. During volar plating pronator quadratus muscle is incised for proper visualization of fracture and reduction. There is always a debate whether to repair the muscle after fixation or not.METHODS: This is a prospective comparative study done in Manipal Teaching Hospital from June 2017 to February 2020. There were total 80 patients included in this study. The total patients were divided into two groups. Group A included the patients who had repair of the pronator quadratus and group B patient did not have repair of pronator quadratus. The aim of our study was to compare the outcome of repair of pronator quadratus muscle to unrepaired group in terms of quick DASH score, grip strength VAS score and ROM post-operatively at 6weeks, 12 weeks, 6 month and 1 year time. Statistical analysis was done using SPSS statistical software version 13.0.RESULTS: There was no statistical difference in quick DASH score, grip strength, visual analog score (VAS) score and range of movement (ROM) in 6 months and 1 year follow up in both the group.CONCLUSION: The repair of pronator quadratus muscle after volar plating does not have additional benefit in functional outcome.